2021
DOI: 10.3996/jfwm-20-072
|View full text |Cite
|
Sign up to set email alerts
|

Embracing Ensemble Species Distribution Models to Inform At-Risk Species Status Assessments

Abstract: Conservation planning depends on reliable information regarding the geographic distribution of species. However, our knowledge of species' distributions is often incomplete, especially when species are cryptic, difficult to survey, or rare. The use of species distribution models has increased in recent years and proven a valuable tool to evaluate habitat suitability for species. However, practitioners have yet to fully adopt the potential of species distribution models to inform conservation efforts for inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 59 publications
0
13
1
Order By: Relevance
“…Additionally, we observed that the prediction accuracy of the XGBoost was very close to that of RF as the XGBoost has good generalization performance 35 . Although, previous studies have shown that MaxEnt, SVM, and GBM models performed well in simulating species suitability distribution 36 , 37 , our results have shown that the prediction accuracy of these models was intermediate relative to the performance of the seven tested models. These phenomena may indicate that species characteristics and sample size also have influence on the accuracy of species distribution models 38 .…”
Section: Discussioncontrasting
confidence: 83%
“…Additionally, we observed that the prediction accuracy of the XGBoost was very close to that of RF as the XGBoost has good generalization performance 35 . Although, previous studies have shown that MaxEnt, SVM, and GBM models performed well in simulating species suitability distribution 36 , 37 , our results have shown that the prediction accuracy of these models was intermediate relative to the performance of the seven tested models. These phenomena may indicate that species characteristics and sample size also have influence on the accuracy of species distribution models 38 .…”
Section: Discussioncontrasting
confidence: 83%
“…Besides, it had 0.99 with TSS and 0.95 in Kappa accuracy evaluation, indicating correctly classifying suitable and unsuitable territories of the world for AHSv. The ensemble model's accuracy metrics were better than individual models indicating the ensemble approach was the best choice than using individual models alone 25 27 . Bioclimatic variables like Solar radiation, mean maximum temperature, mean precipitation of the year, altitude and precipitation seasonality contributed 36.83%, 17.1%, 14.34%, 7.61%, and 6.4%, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…An AUC value of 0.5 is considered poor performance, while 1 would be excellent. Given the relative low number of presence records, we used a jackknife approach (Pearson et al 2007; Ramirez-Reyes et al 2021) where models are constructed using all presence and pseudoabsence records minus one observation ( n - 1). We used the omitted observation's environmental data to solve the n - 1 model and obtain a predicted value.…”
Section: Methodsmentioning
confidence: 99%